Peran Inklusi Keuangan Digital dalam Mengurangi Kemiskinan Systematic Literature Review - Rosyalita, Dita; Aziz, Abdul (Jujurnal Publisher, 2024)
This study aims to analyze the role of digital financial inclusion in reducing poverty, with a particular focus on access to financial services, income improvement, and household economic resilience. The research employs a Systematic Literature Review (SLR) approach, using a structured and rigorous methodology to identify, evaluate, and synthesize relevant academic studies. Primary data are derived from peer-reviewed journal articles, while secondary data include books and institutional reports related to digital financial inclusion, poverty reduction, and financial access. The findings indicate that digital financial inclusion plays a significant role in expanding financial access for previously unbanked populations through technologies such as mobile banking, fintech, and digital wallets. These innovations enhance transaction efficiency, reduce costs, and create broader economic opportunities, particularly for low-income communities. Furthermore, digital financial inclusion contributes to increased household income and improved financial stability, thereby supporting poverty alleviation efforts. However, its effectiveness is influenced by several factors, including financial and digital literacy, digital infrastructure, and supportive government policies. Without these enabling conditions, the impact of digital financial inclusion tends to be uneven across different population groups (Kelikume, 2021; Inoue, 2024). Therefore, a comprehensive and integrated approach is necessary to maximize its benefits. This study contributes to the growing body of literature on digital economy and inclusive development, while also providing practical implications for policymakers in designing effective poverty reduction strategies.